PEMANFAATAN LAPISAN PERKERASAN LAMA SEBAGAI CAMPURAN CTRB PADA RUAS JALAN TELUK BUA KABUPATEN KATINGAN - Rico Febrian; Desriantomy Desriantomy; Ina Elvina (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2025)
Road pavement is one part of road construction. Teluk Bua Road is a very important transportation route for the growth path of various aspects in Katingan Regency. Based on observations made, the Teluk Bua road section is often damaged. Types of road damage that occur include rutting, settlement, and upheaval or swell are characterized by bumpy road surfaces with damage levels from mild to severe. This study aims as a literature study to analyze the performance of the composition of the resulting mixture and analyze the value of free compressive strength of the resulting mixture, as well as to determine the stages of implementation in the field. One of the innovations in cost savings, the Cement Treated Recycling Base (CTRB) method is used in road foundation layer work. In the plan, there are variations in cement content of 7% to be reviewed, namely: The results of the study on the free compressive strength of CTRB cylinders with cement variation materials can be known from the mixture of Existing Material Ex. Teluk Bua (RAP) 65% + Additional Material Foundation Layer Class A Ex.Hampangen 35% + 7% cement added material which is 31.21 kg/ cm2. From this graph, the value of Dry Content Weight (MDD) used is 2.159 gr/m3, Optimum Water Content (OMC) is 6.44%. From the calculation results, the CBR Value of Plan = 86.33%.